18F-FDG PET/CT in the Management of Aortitis. (January 2016) - Bruls, Samuel; Courtois, Audrey; Nusgens, Betty; Defraigne, Jean-Olivier; Delvenne, Philippe; Hustinx, Roland; Moutschen, Michel; Sakalihasan, Natzi
Abstract : Background: Aortitis is a generic term defined as an inflammatory condition involving the aortic wall, of infectious or noninfectious origin. This inflammatory process may deteriorate the aortic wall, resulting in potentially life-threatening vascular complications. Therefore, it is important to establish a diagnosis as early as possible. Patients and Methods: During a 4-year period, 428 consecutive patients referred to our department for aortic diseases underwent FDG PET/CT examinations. Among these, 18 patients (4.2%) were suspected to have aortitis. All of them had an initial positive FDG PET/CT uptake occurring in the aorta and major branches as evaluated by visual analysis of images and assessed with the final diagnosis of aortitis. During follow-up, after surgery and/or upon immunosuppressive treatment, each of these patients underwent a second PET/CT that was compared with the initial evaluation. In all cases, normalization of FDG uptake was correlated with clinical improvement. Conclusions: Our study aimed to illustrate the potential clinical value of functional monitoring with PET/CT in the management of aortitis. FDG PET/CT constitutes a valuable imaging modality to establish an early diagnosis, monitor disease progression and treatment, and evaluate vascular complication and relapse. We highlight the importance of an early detection of inflammatory large-vessel pathology, which may represent a major threat. Abstract : Supplemental digital content is available in the text.